Influential Factors in The Law Enforcement Process of Sexual Violence Cases in Children in The City of Semarang - Liya Suwarni; Tuntas Dhanardhono; Bianti Hastuti Machroes (SOEPRA, 2020)
Abstract:Background. Cases of sexual violence increase every year, victims ranging from adolescents, children to toddlers. Based on data from the Indonesian Child Protection Commission, abuse and violence against children in Indonesia in 2013 were 23 cases, in 2014 there were 53 cases, in 2015 there were 133 cases, 2017 reached 1,337 cases, and as of July 2018 there were 424 cases.Purpose. Knowing the factors that influence the law enforcement process of sexy violence cases in Semarang City.Method This study uses descriptive analytical methods for cases of violence against children, based on medical record data in hospitals, documents in Mapolrestabes, the District Attorney's Office and the Semarang City Court for the period of January 2015 to December 2018.Results. Based on research results obtained 213 experimental cases section from medical record data in hospitals in the city of Semarang. Most cases of child abuse occurred in 2018 with 72 cases. Most victims are 12-14 years old age group, female. Most types of cases are cases of intercourse. The majority of violations are persons known as victims, perpetrators not working, and most of the places of occurrence are in the defendant's house. At the time of prosecution and trial, the number of cases was significantly reduced to only 8 cases. Factors related to this include lack of evidence, difficulty in obtaining information from victims, convoluted statements of coverage, lack of election, and obtaining diversion rates.Conclusion Cases of sexual violence have increased from year to year. The process of law enforcement on this problem still has many difficulties in each manufacturing process which is still difficult to overcome.Keywords; sexual violence, children, law enforcement, Semarang City. AbstrakLatar belakang. Kasus kekerasan seksual mengalami peningkatan setiap tahun, korbannya mulai dari kalangan dewasa, remaja, anak-anak hingga balita. Berdasarkan data Komisi Perlindungan Anak Indonesia, pelecehan dan kekerasan seksual terhadap anak di Indonesia pada tahun 2013 sebanyak 23 kasus, 2014 sebanyak 53 kasus, 2015 sebanyak 133 kasus, 2017 telah mencapai 1.337 kasus, dan hingga bulan Juli 2018 terdapat 424 kasus.Tujuan. Mengetahui faktor-faktor yang mempengaruhi proses penegakkan hukum kasus kekerasan seksual di Kota Semarang.Metode. Penelitian ini menggunakan metode deskriptif analitik terhadap kasus kekerasan seksual pada anak, berdasarkan data rekam medis di Rumah Sakit, dokumen di Mapolrestabes, Kejaksaan Negeri, dan Pengadilan Kota Semarang periode Januari 2015 hingga Desember 2018.Hasil. Berdasarkan hasil penelitian didapatkan 213 kasus kekerasan seksual dari data rekam medis di Rumah Sakit di Kota Semarang. Kasus kekerasan seksual pada anak terbanyak terjadi pada tahun 2018 sebanyak 72 kasus. Korban terbanyak adalah kelompok usia 12-14 tahun, berjenis kelamin perempuan. Jenis kasus terbanyak adalah kasus senggama. Mayoritas pelaku merupakan orang yang dikenal oleh korban, pelaku tidak bekerja, dan tempat kejadian terbanyak adalah di rumah terdakwa. Pada tahap penuntutan dan persidangan, jumlah kasus tersebut berkurang secara signifikan menjadi 8 kasus saja. Faktor-faktor yang terkait menyebabkan hal tersebut antara lain kurangnya alat bukti, sulitnya mendapatkan keterangan dari korban, keterangan pelaku yang berbelit-belit, tidak adanya saksi, dan tingginya angka diversi.Simpulan. Kasus kekerasan seksual meningkat dari tahun ke tahun. Proses penegakkan hukum terhadap kasus ini masih memiliki banyak kendala pada tiap tahap yng masih sulit diatasi.Kata kunci: kekerasan seksual, anak, penegakkan hukum, Kota Semarang.